PENGEMBANGAN METODE BANGKITAN DAN TARIKAN PERJALANAN BERDASARKAN CITRA QUICKBIRD - Dg Bau, Qadriathi; Hartono, Hartono; Parikesit, Danang; Gunawan, Totok (Jurnal Transportasi, 2013)
As a basic model, trip generation model aims to obtain the number of movement generated by each origin and the one attracted to each destination zone. Based on the movement, trip generation model is categorized into home-based trip generation and non home-originated/destinated trip attraction. Given that the different types of activities attract trips with different characteristics, it can be concluded that land use management determines the movement and activities. Remote sensing imagery has been extensively used in various research themes including land use management or land use and detailed land utility. As one of the remote sensing imageries, Quickbird imagery is advantageous with its high spatial resolution which is 0.61 cm. Therefore, it is interesting to apply the 0.61 cm spatial resolution to the trip generation model to estimate the number of trips at the trip generation. This aims is to minimize field activities which are high cost, extensive workers, and relatively time consuming.Keywords: trip generation model, trip attraction, quickbird imagery